Peningkatan Hasil Belajar PAI Pada Siswa Kelas XI Dengan Model Problem Based Learning di SMK N 1 Batipuh - Irvan Darma Putra (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) subjects through the application of the Problem Based Learning (PBL) learning model in class XI of SMK Negeri 1 Batipuh. The method used was Classroom Action Research (PTK) which was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The focus of the research was on the material of Marriage in Islam. The results showed that the application of the PBL model was effective in improving learning outcomes and student activeness. The average class score increased from 72 in cycle I to 80 in cycle II, with the percentage of student completeness increasing from 60% to 85%. In addition, student activeness in discussions and presentations increased significantly. The PBL model not only improved students' academic results but also encouraged the development of critical thinking skills, collaboration, and self-confidence. This study concludes that the application of the PBL model is worth using as an innovative method in PAI learning, especially to improve the quality of education in SMK. It is recommended that teachers utilize this model regularly with structured guidance and relevant teaching materials.